Direct observation of creep strengthening nanoprecipitate formation in ausformed ferritic/martensitic steels. (15th April 2019) - Vivas, J.; De-Castro, D.; Poplawsky, J.D.; San-Martín, D.; Capdevila, C.
Abstract: It is well known the effectiveness of ausforming on increasing the dislocation density of fresh martensite. This work demonstrates, using atom probe tomography, that this increase in the dislocation density has a strong influence on the nucleation of nanoprecipitates during tempering. Therefore, ausforming might be a powerful processing route for the two-fold improvement of ferritic/martensitic steels where creep resistance is of paramount importance. Firstly, ausforming refines the martensitic microstructure (high strength and toughness), and secondly, it increases the number density of thermally stable nanoprecipitates (creep resistance). Graphical abstract: Unlabelled Image